Evaluation of the efficacy and safety of nivolumab in the second- or later-line treatment of patients with locally advanced/metastatic non-small cell lung cancer in Türkiye: a retrospective multicenter non-interventional registry study - YUMUK, PERRAN FULDEN (My University, 2024)
Objective: To evaluate the efficacy and safety of nivolumab in the second-line (2L) or later-line (LL) treatment of patients with locally advanced/metastatic non-small cell lung cancer (NSCLC) in real-life setting in Türkiye. Methods: This study was designed as a national, multi-center, retrospective study. The study population was evaluated in two groups for the line of nivolumab therapy: those receiving nivolumab in the 2L (Group 2L) and third-line (3L) or LL (Group 3L/LL). Efficacy was evaluated based on one-year overall survival (OS) and progression-free survival (PFS). Safety was evaluated based on treatment-related adverse events (AEs) and nivolumab discontinuation rate. Results: Of 244 patients, 52.9% were in Group 2L and 47.1% were in Group 3L/LL. Demographic and clinical characteristics did not differ between the groups. In Group 2L and Group 3L/LL, one-year OS and PFS rates were 60.8% and 61.4% (p = 0.592) and 31.2% and 21.3% (p = 0.078), respectively. The objective response rate (ORR) was 34.7% in Group 2L and 27.3% in Group 3L/LL (p = 0.262). The percentage of patients reporting at least one AE in Groups 2L and 3L/LL was 34.9% and 43.5%, respectively (p = 0.169). Fatigue was the most common (16.4%) treatment-related AE in each group. The groups were comparable regarding the AE frequency. Nivolumab was discontinued in 61 patients in Group 2L and 53 patients in Group 3L/LL, with the most common reason being disease progression (57.4% and 66.0%, respectively). Conclusion: Nivolumab is safe and effective in the 2L or 3L/LL treatment of locally advanced/metastatic NSCLC and associated with acceptable AEs in real-life setting.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; efficacy; Nivolumab; non-small cell lung cancer; safety; second-line therapy